Analisis Dinamika Penelitian Pencemaran Air Sungai berdasarkan Studi Bibliometrik 10 tahun terakhir - Mia Erpinda; Nur Faizaturrohmah; Suci Wulandari (Jurnal Serambi Engineering, 2024)
This study analyses the research dynamics on river water pollution over the last decade (2014-2024) using bibliometric analysis. Data were collected using Publish or Perish software with Google Scholar as the main source, using keywords such as 'river pollution', 'river water quality', 'river contamination' and 'river water pollution'. Articles published between 2014 and 2024 were selected, resulting in a total of 1,000 relevant publications. The bibliometric analysis was conducted using VOSviewer version 1.6.20, which allowed mapping of research trends and visualisation of key themes through network, overlay and density visualisation. The results identified five major clusters in river pollution research, with three dominant themes: "water quality index", "metal pollution" and "microplastics". The overlay visualisation showed an increasing focus on emerging themes such as urbanisation and climate change since 2017, and microplastics as a major concern since 2019. This bibliometric analysis provides valuable insights to guide future research by identifying trends and gaps in river pollution studies. It also supports the development of evidence-based environmental policies and highlights the need for interdisciplinary collaboration to effectively address pressing water pollution challenges.